Case Report: Mucolipidosis II and III Alpha/Beta Caused by Pathogenic Variants in the GNPTAB Gene (Mucolipidosis) - Mao, Shao-Jia; Zu, Yu-Mei; Dai, Yang-Li; Zou, Chao-Chun (Frontiers in Pediatrics, 2022)
Abstract Objective To improve the cognition of mucolipidosis (ML) II and III alpha/beta by analyzing the clinical manifestations of two patients. Methods The clinical, biochemical and molecular data of two clinical cases associated with ML II and III alpha/beta were analyzed and compared with other case reports of ML II and III alpha/beta. Results The first patient was a 14-month-old girl who was hospitalized because of abnormal postnatal coarse facial features. The child had no abnormal birth history but developed multiple abnormalities, such as psychomotor retardation, abnormal facial features, bilateral limb muscle hypotonia, and genital abnormalities. The X-ray of the spine revealed multiple bone malformations. Brain magnetic resonance imaging (MRI) showed delayed myelination. Genetic testing showed the presence of two compound heterozygous pathogenic variants (c.1364C>T and c.1284+1G>T) in the GNPTAB gene. The second patient was an 18-month-old boy who was hospitalized for recurrent respiratory tract infections. The patient was a high-risk preterm infant with postnatal psychomotor retardation, language development retardation, intellectual disability, and coarse facial features. The X-ray showed multiple bone malformations. Craniocerebral ultrasound showed bilateral ventricle widening. Genetic testing showed the presence of two compound heterozygous pathogenic variants (c.1284+1G>T and c.483delT) in the same gene. Conclusions ML II and III alpha/beta are rare autosomal recessive lysosomal storage diseases that are attributed to GNPTAB variants that cause N-acetylglucosamine-1-phosphotransferase deficiency, and finally lead to multiple clinical signs and symptoms. A proper ML II and/or III alpha/beta diagnosis requires a combined analysis of the patients’ clinical manifestations, imaging examination, enzymatic analysis and genetic testing results. Ultimately, genetic counseling is essential for this disease.